2023
DOI: 10.1027/0227-5910/a000903
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Experiences of Orphans and Left-Behind Children in China as Predictors of Suicidal Thoughts and Behaviors

Abstract: Background: Suicide has been recognized as a serious problem in orphans and left-behind children. It is important to examine the differences in the factors affecting suicidal thoughts and behaviors between the two groups. Aims: To compare the lifetime rates of suicidal thoughts and behaviors between orphans, left-behind children, and other children, and to assess the impact of discrimination experiences and the mediating role of self-esteem. Methods: A total of 2,413 children from middle schools in China compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…To our knowledge, this study marks the first qualitative exploration of how parental migration and its associated factors affect the social and mental well-being of LBC in Indonesia. Parental labour migration or the absence of one or both parents in LBC’s lives has negative social consequences, including stigma and discrimination against them, which have been associated with increased stress, depression, and suicidal ideation and behaviours among them [ 46 , 47 , 48 ]. Our findings echo these social consequences, highlighting the negative impact of one or both parents’ migration on LBC’s social well-being reflected in withdrawal from or broken social relationships with peers.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study marks the first qualitative exploration of how parental migration and its associated factors affect the social and mental well-being of LBC in Indonesia. Parental labour migration or the absence of one or both parents in LBC’s lives has negative social consequences, including stigma and discrimination against them, which have been associated with increased stress, depression, and suicidal ideation and behaviours among them [ 46 , 47 , 48 ]. Our findings echo these social consequences, highlighting the negative impact of one or both parents’ migration on LBC’s social well-being reflected in withdrawal from or broken social relationships with peers.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis study showed that the incidence of severe mental health status of left‐behind children in China was higher than that of the non‐left‐behind group (Wu et al, 2019). Additionally, one study comparing orphans and left‐behind adolescents revealed that left‐behind adolescents had even higher suicidal ideation than orphans (Guo & Li, 2023).…”
Section: Methodsmentioning
confidence: 99%